2007
DOI: 10.1158/0008-5472.can-06-4356
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Role of KIAA0101 Interacting with Proliferating Cell Nuclear Antigen in Pancreatic Cancer

Abstract: To isolate novel diagnostic markers and therapeutic targets for pancreatic cancer, we earlier did expression profile analysis of pancreatic cancer cells using a genome-wide cDNA microarray combined with microdissection. Among dozens of trans-activated genes in pancreatic cancer cells, this study focused on KIAA0101 whose overexpression in pancreatic cancer cells was validated by immunohistochemical analysis. KIAA0101 was previously identified as p15 PAF [proliferating cell nuclear antigen (PCNA)-associated fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
128
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(137 citation statements)
references
References 24 publications
(42 reference statements)
7
128
1
Order By: Relevance
“…Tandem mass spectroscopy (MS/MS) identified copurifying proteins. Accordingly, we identified PCNA as having a strong interaction with PAF15, as has been reported by others (11)(12)(13)(14). Silver staining of the immunoprecipitates together with MS/MS data suggested that PAF15 is stoichiometrically associated with PCNA in a 1:1 complex (Fig.…”
Section: Paf15supporting
confidence: 85%
“…Tandem mass spectroscopy (MS/MS) identified copurifying proteins. Accordingly, we identified PCNA as having a strong interaction with PAF15, as has been reported by others (11)(12)(13)(14). Silver staining of the immunoprecipitates together with MS/MS data suggested that PAF15 is stoichiometrically associated with PCNA in a 1:1 complex (Fig.…”
Section: Paf15supporting
confidence: 85%
“…We further show that p15 PAF constitutes a major effector of ATF3 for DNA repair. Although p15 PAF downregulation seems to be dependent on the p53-p21 pathway, 18 we show here, that after UV treatment, ATF3 is directly responsible for p15 PAF expression. p15 PAF also known as PCNA-associated factor, KIAA0101 or OEATC-1, 16,17 has been shown to localize to the mitochondria and the nucleus.…”
Section: Discussioncontrasting
confidence: 48%
“…It is therefore tempting to speculate that the lack of ATF3 expression contributes to the impaired DNA damage response responsible for oncogenesis. Although upregulation and oncogenic function of p15 PAF has been described in esophageal tumors 17 and in pancreatic cancer, 18 a putative tumor suppressor function has been suggested by its downregulation in several human colorectal tumors and hepatocellular carcinoma. 16,27 As the downregulation does not appear to be related to mutations, 16 it is possible that reduction in the levels of p15 PAF is mediated by the lack of ATF3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of p15 correlates with tumour progression and poor prognosis in a number of human cancers [13][14][15][16] . Evidence for p15-PCNA interaction comes from yeast two-hybrid and co-immunoprecipitation experiments, but no structural detail of the direct interaction is known.…”
mentioning
confidence: 99%